Techniques Of English Teaching Used At SMP Muhammadiyah 5 Surakarta: A Naturalistic Study - Revellia, Shelvita; , Prof. Dr. Endang Fauziati, M. Hum; , Dr. Dwi Haryanti, M.Hum (2014)
The aims of this research are to analyze (1) the kinds of English teaching techniques used by the teacher in SMP Muhammadiyah 5 Surakarta, (2) the objectives of English teaching-learning process of using these techniques, (3) the teacher's roles, (4) the learner's roles, (5) the dominant techniques used by the teacher in SMP Muhammadiyah 5 Surakarta. The research is a naturalistic study. There are three sources of data in this research namely event, informant and document which related with teaching-learning process of SMP Muhammadiyah 5 Surakarta. Methods of collecting data in this research are observation, interview and document. The object of this research is focused on the techniques applied by the teacher in teaching learning process of English. The data are analyzed by a naturalistic study which consists of collecting data, data reduction, display data and conclusion. This research uses data validity to prove the validity of the research namely data triangulation, investigator triangulation, theoretical triangulation and methodological triangulation. The research concludes there are four techniques implemented by the teacher in teaching learning process of English of SMP Muhammadiyah 5 Surakarta. The techniques are namely reading aloud, oral repetition, answering question and dialog conversation. In reading aloud, the objective is students are able to respond to the text read out by the teacher. In Oral Repetition, the objective that it is an effective way to solve problems faced by the students in learning pronunciation. In Answering Question, the objective is students understand and able to identify main point about of the text. And in Dialog Conversation, the objective is can form the character of students more confident, not shy and dare to appear in front of other students. The most dominant technique used in SMP Muhammadiyah 5 Surakarta is answering question and dialog conversation.